Wnt/β-Catenin Signalling during Liver Metabolism, Chronic Liver Disease and Hepatocarcinogenesis (Journal of Renal and Hepatic Disorders, 2018)
Chronic liver diseases (CLDs) are increasing in prevalence and their end-stage complications, namely, cirrhosis, liver failure and hepatocellular carcinoma represent major global challenges. The most common initiators of progressive CLD are viral hepatitis and long-term alcohol abuse as well as steatosis and steatohepatitis. Irrespective of the underlying aetiology, a common feature of CLD is the formation of hepatic ductular reactions, involving the proliferation of liver progenitor cells (LPCs) and their signalling to fibrosis-driving hepatic stellate cells. The Wnt/β-catenin pathway has been found to regulate development, stemness and differentiation, and alterations in its activity have been associated with tumour development. Recent data highlight the role of Wnt/β-catenin signalling in hepatic metabolism, steatosis and cancer, and suggest targeting of this pathway as a promising molecular strategy to potentially inhibit CLD progression and hepatocarcinogenesis.
Keywords: chronic liver disease; hepatocellular carcinoma; liver progenitor cells; metabolic syndrome; Wnt/β-catenin signalling